Investigation of the effect of intravitreal bevacizumab treatment on left heart function using speckle tracking echocardiography - Mehmet Şahinbaş; İdris Buğra Çerik; Duygu Yalınbaş Yeter (Revista Portuguesa de Cardiologia)
Introduction and objectives: Vascular endothelial growth factor (VEGF) inhibitors are widely used in oncology and ophthalmology. Although these agents have been shown to increase the risk of cardiovascular events in systemic use, the effect of local applications is unclear. In our study, we aimed to investigate the effects of anti-VEGF agents on left heart functions after intravitreal injection using speckle tracking echocardiography. Methods: In this prospectively designed study, 44 patients who were going to start intravitreal anti-VEGF treatment were included in the study. Patients were evaluated with speckle tracking echocardiography before the first anti-VEGF administration and at three months of anti-VEGF treatment. Results: Global longitudinal strain (GLS) values at three months were lower in the patients who participated in the study and this was statistically significant (−18.77±2.17, −18.60±2.01, p=0.001). Also, there was a statistically significant decrease in the mean values of GLS (GLS4CH) obtained from apical four space image, GLS (GLSAPLAX) obtained from apical long axis image and GLS (GLS2CH) obtained from apical 2 space image at month 0 and month 3 (−19.08±2.39, −18.93±2.26, p=0.004; −18.81±2.29, −18.60±2.12, p=0.001; −18.44±2.31, −18.27±2.12, p=0.013, respectively). Conclusion: The slight decrease in GLS in our study suggests that the use of intravitreal anti-VEGF agents may have cardiac effects. Resumo: Introdução e objetivos: Os inibidores do fator de crescimento endotelial vascular (FCEV) são amplamente utilizados em oncologia e oftalmologia. Embora tenha sido demonstrado que estes agentes aumentam o risco de eventos cardiovasculares no uso sistémico, o efeito das aplicações locais não é claro. No nosso estudo, o nosso objetivo foi investigar os efeitos dos agentes anti-FCEV nas funções do coração esquerdo após injeção intravítrea (IVI) por meio da ecocardiografia com speckle tracking. Métodos: Neste estudo prospetivo, 44 pacientes que iriam iniciar tratamento intravítreo anti-FCEV foram incluídos no estudo. Os pacientes foram avaliados com ecocardiografia com speckle tracking antes da primeira administração de anti-FCEV e aos três meses de tratamento anti-FCEV. Resultados: Os valores do global longitudinal strain (GLS) aos três meses foram menores nos pacientes que participaram do estudo e isso foi estatisticamente significativo (−18,77 ± 2,17, −18,60 ± 2,01, p = 0,001). Além disso, houve uma diminuição estatisticamente significativa nos valores médios de GLS (GLS4CH) obtido da imagem do espaço apical 4, GLS (GLSAPLAX) obtido da imagem apical do eixo longo e GLS (GLS2CH) obtido da imagem do espaço apical 2 no mês 0 e mês 3 (−19,08 ± 2,39, −18,93 ± 2,26, p = 0,004; −18,81 ± 2,29, −18,60 ± 2,12, p = 0,001; −18,44 ± 2,31, −18,27 ± 2,12, p = 0,013, respetivamente). Conclusão: A ligeira diminuição do GLS observada no nosso estudo sugere que o uso de agentes anti-FCEV intravítreos pode ter efeitos cardíacos.